Features of psychological training in the NATO Аrmies: an analytical review - Kravchenko, Kateryna; Babich, Oksana; Sokolina, Olha; Yurkova, Olha; Belichenko, Liudmyla (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
Background. Under the current conditions of full-scale warfare, Ukraine is facing unprecedented psychological demands on its military personnel. This necessitates scientifically grounded and systematic approaches to psychological training that foster resilience to combat stress and ensure the ability to operate effectively under extreme conditions. The experience of the NATO member states′ armies ‒ where psychological training is fully integrated across all levels of combat instruction – serves as an important benchmark for developing Ukraine′s own system of preparing its military personnel to meet the psychological challenges of war. This highlights the relevance of studying the specific features of psychological training in the NATO armed forces. Research Objective – to explore the distinctive features of psychological training in the NATO armed forces and to formulate recommendations for enhancing the psychological preparation of the personnel of the Armed Forces of Ukraine. Methods. The study employed theoretical research methods, including analysis, synthesis, generalization, comparison, and systematization. Results. It was established that psychological training of military personnel in NATO countries is structured as an integrated, multi-level, and scientific evidence-based approach. It includes the development of adaptive thinking, self-regulation skills, team cohesion, psychological leadership, and other critical components required to build psychological resilience and combat readiness. Key trends include the integration of psychological training into combat instruction; digitalization (use of VR environments and biofeedback technologies); and continues monitoring of personnel′s mental state, etc. At the same time, several challenges were identified, such as fragmentation in standards, time constraints, insufficient practical orientation in some training courses, and uneven implementation among Allied nations. Conclusions. The psychological training system of NATO armies is well-developed and has proven its effectiveness in both local conflicts and peacekeeping operations. However, NATO′s experience cannot be fully implemented into the Ukrainian context without substantial adaptation. Ukraine′s unique operational environment requires the development ‒ or refinement ‒ of a national psychological training model. While this model should align with NATO principles, it must also account for the intensity of combat operations, the scale of non-combat losses, the absence of rotations, duration of the strain, the involvement of mobilized personnel, and the motivational and value-driven patriotic defense factors. Where necessary, such adaptations must be profound ‒ taking precedence over NATO standards ‒ since they determine the psychological resilience and combat readiness of Ukrainian military personnel in the realities of contemporary warfare.